Implementation of the Use of Daily Journals in PAUD Institutions - Amelia, Zahrina; Pansuri, Fitria Farhani (Universitas Negeri Semarang, 2021)
One strategy to encourage children's early literacy skills, especially those aged 3-5 years, is to keep a daily journal so that children can communicate their thoughts, feelings and record their ideas through scribbles or pictures. Furthermore, scientific studies show that expressing what a person thinks and feels in a journal can have a positive impact on the author's physical and mental health. Based on the previous research, the researcher was interested in seeing how the